A Simple Proof of Euler’s Formula

Euler’s formula (well, one of Euler’s formulas) states that e^{i \theta} = \cos \theta + i \sin \theta.  The proof I am most familiar with is based on the Maclaurin series for e^x, \sin x, and \cos x.

I ran across a different, simpler proof recently on Math Stack Exchange, posted by user02138.  It doesn’t give any insight into why the formula is true, but it is very short.

Let f(\theta) = e^{- i \theta} (\cos \theta + i \sin \theta).  Then f'(\theta) = -i e^{-i \theta} (\cos \theta + i \sin \theta) + e^{- i \theta} (- \sin \theta + i \cos \theta).  Simplifying, we have f'(\theta) = e^{- i \theta} ( - i \cos \theta + \sin \theta - \sin \theta + i \cos \theta ) = 0.  The fact that f'(\theta) = 0 implies that f(\theta) = C for some constant C.  Since f(0) = e^0 (\cos 0 + i \sin 0) = 1, f(\theta) = 1, and thus e^{i \theta} = \cos \theta + i \sin \theta.

Some of the other answers to “How to prove Euler’s formula” are interesting and worth perusing as well.

Advertisements
This entry was posted in complex numbers. Bookmark the permalink.

Leave a Reply

Fill in your details below or click an icon to log in:

WordPress.com Logo

You are commenting using your WordPress.com account. Log Out / Change )

Twitter picture

You are commenting using your Twitter account. Log Out / Change )

Facebook photo

You are commenting using your Facebook account. Log Out / Change )

Google+ photo

You are commenting using your Google+ account. Log Out / Change )

Connecting to %s